INTEGRATING BANK SIZE, LIQUIDITY, AND FINANCIAL PERFORMANCE INTO MODERATING FINANCIAL TECHNOLOGY: A CASE STUDY OF SHARIA COMMERCIAL BANKS IN INDONESIA - Hermuningsih, Sri; Rahmawati, Anisya Dewi (Universitas Brawijaya, Indonesia, 2022)
A company evaluates each profit-generating success to understand the organization's growth, prospects, and potential developments. If a business meets the established goals and standards, it can be said to succeed. This study examines and demonstrates how bank size and liquidity affect financial performance in Indonesia's Islamic Commercial Banks using Financial Technology (Fintech). This moderating factor connects the Financial Services Authority from 2016 to 2021, which constitutes the study's population. The sample was drawn from Islamic Commercial Banks using Fintech between 2016 and 2021. The sampling procedure used purposeful sampling with the requirements of Islamic Commercial Banks that incorporated Fintech to obtain data from 12 Islamic Commercial Banks with 76 financial statement data. SmartPLS software (PLS-SEM method) is used for the analysis process. The findings of this study show that bank size and liquidity positively affect financial performance. Applying Fintech by Indonesia's Islamic Commercial Banks improves their impact on earnings management. Due to the size of the bank and more liquidity, such financial performance will consequently enhance the chances of adopting Fintech. This empirical data shows that Indonesia's Islamic Commercial Banks' adoption of Fintech is unprecedented.